Advances in Intelligent Systems and Interactive Applications Proceedings of the 2nd International Conference on Intelligent and Interactive Systems and Applications (IISA2017) (Advances in Intelligent Systems and Computing,, 2018)
This book presents research papers from diverse areas on novel Intelligent Systems and Interactive Systems and Applications. It gathers selected research papers presented at the 2nd International Conference on Intelligent and Interactive Systems and Applications (IISA2017), which was held on June 17-18, 2017 in Beijing, China. Interactive Intelligent Systems (IIS) are systems that interact with human beings, media or virtual agents in intelligent computing environments. The emergence of Big Data and the Internet of Things have now opened new opportunities in both academic and industrial research for the successful design and development of intelligent interactive systems. This book explores how novel interactive systems can be used to overcome various challenges and limitations previously encountered by human beings by combining machine learning algorithms and the analysis of recent trends. The book presents 125 contributions, which have been categorized into seven sections, namely: i) Autonomous Systems; ii) Pattern Recognition and Vision Systems; iii) E-Enabled Systems; iv) Mobile Computing and Intelligent Networking; v) Internet and Cloud Computing; vi) Intelligent Systems, and vii) Various Applications. It not only offers readers extensive theoretical information on Intelligent and Interactive Systems, but also introduces them to various applications in different domains.